The Influence of Online Marketing on Online Purchasing Decisions - Yanpitak, Pittayush (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Electronic commerce business. Electronic commerce business (E-Commerce) is transactions made through electronic media in every form and every electronic channel. Thailand can now be said to have entered full online sales because from 2020-2022 Covid (COVID-19) was a factor that made going online in Thailand possible for people at all levels. Thus, the objective of this research is to study the influence of online marketing on consumers’ decision to purchase products online in Thailand. The sample group used in this study consists of internet users residing in Thailand who have previously made online purchases. Methodology: The sample size was determined using the formula by Cochran-W.G. (1977), resulting in a sample size of 385 individuals. The researchers increased the sample size to a total of 400 individuals. The research tool used was an online questionnaire administered through the Google Forms website, with the reliability of the questionnaire assessed using Cronbach’s Alpha Analysis Test. The statistical analysis used to analyze the data included descriptive statistics, simple regression analysis, and multiple regression analysis for hypothesis testing, with a significance level set at 0.05. Results: The majority of respondents in the sample group were female, aged between 21-30 years old, working in the private sector, with an average monthly income of 10,000-20,000 Baht. They decided to purchase products online because of the lower prices compared to traditional markets. They made their own purchasing decisions, with a frequency of at least 7 times per month, and the average price per purchase ranged from 501-1,000 Baht. The main reason for choosing online shopping was convenience, as they could make purchases 24 hours a day through their smartphones, with a preference for making purchases between 20:01 and 24:00. They primarily purchased household products through the Shopee platform. Conclusion: The results also indicated that digital marketing through email advertising and social media had a positive impact on the consumer’s decision to purchase products online in the Bangkok Metropolitan Area and its surrounding provinces, with a statistically significant level of 0.05. This research also highlighted the significant impact of digital marketing, including social media marketing and mobile marketing, on the consumer’s decision to purchase. Ultimately, companies need to strategize and adapt to the digital world and technology, as well as enhance brand recognition through online media to compete in the current business environment.